1991
DOI: 10.1021/ed068p486
|View full text |Cite
|
Sign up to set email alerts
|

A numerical method to calculate equilibrium concentrations for single-equation systems

Abstract: 126. Bits and pieces, 46. A numerical method to calculate equilibrium concentrations for single-equation systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

1993
1993
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…As a consequence the iteration defined by yi+i = F(yi) (7) has a fixed point at the desired equilibrium value ye. Otherwise, two consecutive iterates establish an upper and lower bound toye-If y;+i = y, or the absolute value of the difference is less than a convergence criterion, then a solution of the problem has been found.…”
Section: G(y)=ymentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence the iteration defined by yi+i = F(yi) (7) has a fixed point at the desired equilibrium value ye. Otherwise, two consecutive iterates establish an upper and lower bound toye-If y;+i = y, or the absolute value of the difference is less than a convergence criterion, then a solution of the problem has been found.…”
Section: G(y)=ymentioning
confidence: 99%
“…If acceptable convergence2 is not reached in a small number, say four or five iteration steps, a change of method is indicated. For the best available y,, evaluate y;+i = F(y;) and yi+2 = /''(y.+i), and calculate the next y by the expres-sion3 ynext yti -yffM 2yl-i~yi~yi+2 (7) For typical chemical problems, the convergence by this method is fast and assured.…”
mentioning
confidence: 99%
“…Figure 6 presents a special example of hi nary-mixture analysis as the spectrophotometric determination of equilibrium constants possible when the conjugate variables each have characteristically different spectra. By this technique, it is possible to determine the pifa spectrophotometrically with far greater reliability than that obtained using most potentiometric methods; it also provides a means of calibrating glass electrodes accurately (2). Literature Cited Given the equilibrium constant for a reaction as written and the initial concentrations or partial pressures of all the species involved, what will be the concentrations or partial pressures of various species once the reaction reaches its equilibrium position?…”
Section: Multicomponent Spectrophotometric Analysismentioning
confidence: 99%
“…The equilibrium concentrations of various species are governed by the extent of the of papers Weltin has demonstrated that the extent of a reaction and the equilibrium concentrations are uniquely de-termined by initial concentrations (1)(2)(3). He has suggested the bisection method for calculating the equilibrium extent of a reaction (2). A BASIC program for the bisection method has recently been published by Campanario and Ballesteros (4).…”
Section: Multicomponent Spectrophotometric Analysismentioning
confidence: 99%
“…The program works by minimizing the Gibbs Free Energy as a function of the extent of reaction using an iterative algorithm. This method for single step equilibria (5,6) has been extended to competing and coupled reactions (7).…”
Section: Equilibrium Calculatormentioning
confidence: 99%